2020
DOI: 10.24018/ejmed.2020.2.4.326
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Extended Spectrum Beta-lactamases Producing Escherichia coli and Klebsiella Species in Catheterized Patients

Abstract: Irrational antibiotics use has added to the escalation of antibiotics resistance, especially among hospitalized patients on prolonged urethral catheterization, a significant risk factor for urinary tract infection and urosepsis. Extended-spectrum β-lactamases are transferable plasmid-mediated resistance mechanism orchestrated majorly by Enterobacteriaceae, which confer resistance to β- lactam antibiotics and other classes of antibiotics. This work was aimed at determining the molecular characteristics of uropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…There was no case of polymicrobial CAUTI, attributable to the fact that the durations of catheterization of participants in the study were in the short term range of <30 days [24] The isolates of CAUTI in this study were majorly E. coli (32.7%), Pseudomonas aeruginosa(25%), Klebsiella pneumoniae (15.4%), C. albicans (7.6%), Proteus mirabilis (5.8%), Staphylococcus aureus (3.8%), Coagulase Negative Staphylococcus (1.9%) and Enterococcus faecalis (1.9%). This array of isolates conformed with the microbial growth pattern in short term catheterization [25] In all, E. coli (32.7%) was the dominant isolate in this study and this is similar to the result of a related study in Dhaka, Bangladesh [26] but different from the finding in a similar study [27] at the Lagos University Teaching Hopital, Lagos, Nigeria which reported Klebsiella pneumoniae as the dominant isolate.…”
Section: Discussionsupporting
confidence: 84%
“…There was no case of polymicrobial CAUTI, attributable to the fact that the durations of catheterization of participants in the study were in the short term range of <30 days [24] The isolates of CAUTI in this study were majorly E. coli (32.7%), Pseudomonas aeruginosa(25%), Klebsiella pneumoniae (15.4%), C. albicans (7.6%), Proteus mirabilis (5.8%), Staphylococcus aureus (3.8%), Coagulase Negative Staphylococcus (1.9%) and Enterococcus faecalis (1.9%). This array of isolates conformed with the microbial growth pattern in short term catheterization [25] In all, E. coli (32.7%) was the dominant isolate in this study and this is similar to the result of a related study in Dhaka, Bangladesh [26] but different from the finding in a similar study [27] at the Lagos University Teaching Hopital, Lagos, Nigeria which reported Klebsiella pneumoniae as the dominant isolate.…”
Section: Discussionsupporting
confidence: 84%
“…ESBLs are plasmid‐encoded enzymes that cause resistance to extended‐spectrum cephalosporins, monobactams and aztreonams (CDC, 2019 ). Recently, an increase in ESBL‐producing Enterobacteriaceae has been observed globally (Ushie et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increase in ESBL-producing Enterobacteriaceae has been observed globally (Ushie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%